ASAL-USUL PENAMAAN NAMA-NAMA JORONG DI KANAGARIAN BATUKAMBIANG KECAMATAN AMPEK NAGARI KABUPATEN AGAM - Arneti, Arneti; Hayati, Yenni; Nst., Muhammad Ismail (Universitas Negeri Padang, 2017)
This study discusses the origins of naming names in Kanagarian Jorong Batukambiang Agam District of AmpekNagari. This study aimed to describe the origins, values, and the function of the origin of naming names in Kanagarian Jorong Batukambiang Agam District of Ampek Nagari. Theoretical framework used are: (1) the nature of folklore, (2) forms of Indonesian folklore, (3) a legend as one of the oral folklore, (4) the values of the legend, and (5) the function of oral literature. The research methodology used descriptive method. Data collection techniques used is a literature study, recording, and take note. Based on the research, it can be concluded that four origins of naming names in Kanagarian Jorong Batukambiang Agam District of Ampek Nagari, among other things, that: Jorong Parik, Jorong Balai Badak, Jorong Pasar Batukambiang, and Jorong Alahan Siriah. Based on the findings, naming the origin Jorong Parik fall into the category of natural phenomena. Naming Jorong Balai Badak fall into the category of animals fauna that a rhino. Naming Jorong Pasar Batukambiang fall into the category of topography namely an inanimate object such as a stone. Naming Jorong Alahan Siriah fall into the category flaura namely siriah plants. In naming the origin of the ellipse in Kanagarian Batukambiang, found the value of moral and social values, while the legend for the function is as educate the community, as a collective pride as well as a tool firm of belief.Keywords: origins, values, functions and categories